Rancang Bangun Jaringan Komputer LAN Berdasarkan Perbandingan Kinerja Routing Protokol EIGRP dan Routing Protokol OSPF - Lalu Zazuli Azhar Mardedi; Khairan Marzuki (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
Nowadays computer networks are growing rapidly and internet usage is increasing everyday. The need to design an internet network cannot be separated from the routing protocol which functions to integrate all computers with the highest flexibility. Routing is one part that provides effective performance in the network. In comparing the performance of EIGRP and OSPF routing protocols, the implementation of EIGRP and OSPF must be implemented when building a network, so administrators easily know the difference in the performance values of the two routing protocols. The discussion in this study is to compare the performance of the EIGRP routing protocol and OSPF routing protocol that is on the network using the hybird topology. Overcoming problems with high-scale network access, we will analyze and compare performance between EIGRP routing protocol and OSPF routing protocol. In obtaining the value and to verify the results of the implementation, the simulation software uses a Packet Tracer simulator.